2017
DOI: 10.1142/s0129055x17500192
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of a model for quantum friction

Abstract: An otherwise free classical particle moving through an extended spatially homogeneous medium with which it may exchange energy and momentum will undergo a frictional drag force in the direction opposite to its velocity with a magnitude which is typically proportional to a power of its speed. We study here the quantum equivalent of a classical Hamiltonian model for this friction phenomenon that was proposed in [11]. More precisely, we study the spectral properties of the quantum Hamiltonian and compare the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This model happens to be substantially simpler to study than the Nelson model, precisely due to the fact that vibration fields are uncoupled in space, and we shall thus be able to further treat the case of massless bosons for this model. In the sequel, we aim at a detailed understanding of friction effects in the weak coupling regime, improving on previous results in [9]. 1.3.1.…”
Section: Introduction and Main Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…This model happens to be substantially simpler to study than the Nelson model, precisely due to the fact that vibration fields are uncoupled in space, and we shall thus be able to further treat the case of massless bosons for this model. In the sequel, we aim at a detailed understanding of friction effects in the weak coupling regime, improving on previous results in [9]. 1.3.1.…”
Section: Introduction and Main Resultsmentioning
confidence: 83%
“…The same analysis can be repeated for instance for Fröhlich's polaron model [33]. -For the quantum friction model with massless bosons introduced in [5,9], previous results were also limited by the lack of regularity [9]. Appealing to our modification procedure, we cure again all regularity issues and reduce to the application of regular Mourre theory.…”
Section: Introduction and Main Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Complementary studies of the model (1a)-(1b) can be found in [1,11,12,13,27,32], with connections to stochastic homogenization and to the classical Lorentz problems. We also refer to [8] for a quantum version of the model, and further connection to the Cherenkov radiation.…”
Section: |→+∞mentioning
confidence: 99%